The Urgency of Harmonizing Consumer Protection Law in the Era of Digital Economy and Market Globalization - Wulandari, Bernadetta Tjandra; Arif Awaludin; Indriasari, Evy (Journal of Law, Politic and Humanities, 2025)
The rapid growth of the digital economy and the globalization of markets has highlighted significant gaps in consumer protection laws. These gaps pose challenges in ensuring consumers’ rights and safety in an increasingly digital and interconnected marketplace. This study aims to analyze the urgency of harmonizing consumer protection laws, with a particular focus on issues such as data privacy, cross-border e-commerce, and technological advancements. Using a qualitative research methodology with a literature study approach, this research gathers data from academic journals, reports, and other reputable sources. The findings reveal that current consumer protection laws are inadequate in addressing the complexities of the digital age, with fragmentation in regulations across different jurisdictions leading to legal uncertainty and consumer vulnerability. The lack of international cooperation further exacerbates the issue, making it imperative for countries to work together to create standardized consumer protection frameworks. The study concludes that harmonizing consumer protection laws is crucial for fostering trust in digital markets, protecting consumers, and promoting a fair global digital economy. Further research is recommended to evaluate the practical implications of international cooperation and explore how emerging technologies, such as AI and blockchain, can be regulated to ensure ethical and consumer-friendly practices.